1999
DOI: 10.1038/sj.leu.2401478
|View full text |Cite
|
Sign up to set email alerts
|

A randomized study of granulocyte colony-stimulating factor applied during and after chemotherapy in patients with poor risk myelodysplastic syndromes: a report from the HOVON Cooperative Group

Abstract: The purpose of this study was to determine the safety and efficacy of filgrastim as an adjunct to induction and consolidation chemotherapy in poor risk patients with myelodysplastic syndrome (MDS). Filgrastim was given both during and after chemotherapy with the objective to accelerate hematopoietic repopulation and enhance the efficacy of chemotherapy. In a prospective randomized multicentre phase II trial, a total of 64 patients with poor risk primary MDS were randomized to receive either granulocyte colony-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 13 publications
(19 reference statements)
1
17
0
Order By: Relevance
“…In this setting they have been associated with trends toward improved response rates and survival which were not statistically significant. 17,25 There is less published experience with growth factor priming before and during attenuated dosing regimens for AML or MDS. Furthermore, compared with lowdose cytarabine, intensive chemotherapy does not prolong survival in elderly AML patients due to an increased early death rate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this setting they have been associated with trends toward improved response rates and survival which were not statistically significant. 17,25 There is less published experience with growth factor priming before and during attenuated dosing regimens for AML or MDS. Furthermore, compared with lowdose cytarabine, intensive chemotherapy does not prolong survival in elderly AML patients due to an increased early death rate.…”
Section: Discussionmentioning
confidence: 99%
“…Response criteria were similar to those of other investigators. 17,20 Complete response (CR) was defined as achievement of all the following: reduction of bone marrow blasts and peripheral blasts to less than 5% and 1%, respectively; sustained neutrophil count Ͼ1000/mm 3 for at least 4 weeks; sustained platelet count Ͼ100 000/mm 3 for at least 4 weeks; reduction by Ͼ50% of red blood cell (RBC) transfusion requirements over a period of 4 weeks. Partial response (PR) was defined as achievement of any one of the following: a sustained (4 weeks) increase of neutrophils of at least 100% or more than 1000/mm 3 in patients with pretreatment ANC of less than 1000/mm 3 , a sustained increase in platelet count of at least 100% or more than 50 000/mm 3 in patients with pretreatment platelet count of less than 100 000/mm 3 , or a reduction of the bone marrow blasts by 50%.…”
Section: Response Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…1 To optimize results of standard chemotherapy, the use of G-CSF or GM-CSF concurrently with induction chemotherapy has been studied in several randomized trials. [2][3][4][5][6][7][8][9][10][11][12][13][14][15] The primary intent of these studies has been to sensitize the leukemic cells to the cytotoxic effects of the chemotherapeutic agents. 16 In vitro studies with AML cells had demonstrated that priming with granulocytic hematopoietic growth factors, such as GM-CSF, G-CSF, and IL-3, may critically modulate cell cycle kinetics of AML blasts and render them more susceptible to the cytotoxicity of chemotherapy, especially of the cell cycle specific compound cytarabine.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 A number of studies have addressed this concept in AML patients. [2][3][4][5][6][7][8][9][10][11][12][13][14][15] All these reports show that stimulation of leukemia or prolonged cytopenias resulting from sensitization of normal progenitor cells do not appear as major problems.…”
Section: Introductionmentioning
confidence: 99%